Defect segregation and optical emission in ZnO nano- and microwires. Issue 14 (18th March 2016) - Ruane, W. T.; Johansen, K. M.; Leedy, K. D.; Look, D. C.; von Wenckstern, H.; Grundmann, M.; Farlow, G. C.; Brillson, L. J.
Abstract : The spatial distribution of defect related deep band emission in zinc oxide nano- and microwires using depth resolved cathodoluminescence spectroscopy. Abstract : The spatial distribution of defect related deep band emission has been studied in zinc oxide (ZnO) nano- and microwires using depth resolved cathodoluminescence spectroscopy (DRCLS) in a hyperspectral imaging (HSI) mode within a UHV scanning electron microscope (SEM). Three sets of wires were examined that had been grown by pulsed laser deposition or vapor transport methods and ranged in diameter from 200 nm–2.7 μm. This data was analyzed by developing a 3D DRCLS simulation and using it to estimate the segregation depth and decay profile of the near surface defects. We observed different dominant defects from each growth process as well as diameter-dependent defect segregation behavior.